A Rare Presentation of Concurrent Scedosporium apiospermum and Madurella grisea Eumycetoma in an Immunocompetent Host - Vivek Gulati; Seun Bakare; Saket Tibrewal; Nizar Ismail; Junaid Sayani; Davinder Paul Singh Baghla (Case Reports in Pathology)
Mycetoma is a disfiguring, chronic granulomatous infection which affects the skin and the underlying subcutaneous tissue. We present an atypical case of recurrent mycetoma without ulceration, in a 35-year-old immunocompetent male caused by Scedosporium apiospermum sensu stricto and Madurella grisea, occurring at two separate anatomical sites.